The Relationship Between Learning Motivation and Learning Outcomes of Grade II Elementary School Students - Heriyanti, Meristiya; Firmansah, Deri; Yanti, Yuli (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
The more tall motivation Study a students, increasingly big possibility they For reach results optimal learning. Therefore that's important For understand how far the relationship between motivation Study with results learn to be able to designing more educational strategies​ effective in increase results Study participant educate. Research This aiming For know connection between motivation Study with results Study participant educate class II of elementary school. The research method used in this study uses a quantitative approach with a correlation research type. The population in this study was all class II SDN 2 Karanganyar Jati Agung A total of 32 participants didik. The data collection tools used were questionnaires and tests. The prerequisite tests used were normality test and linearity test. The data analysis technique in this study used the Pearson correlation test. Based on study obtained results that there is significant relationship​ motivation Study participant educate with results Study participant educate class II of SDN 2 Karanganyar Jati Agung.